2014
DOI: 10.1080/09712119.2014.978785
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monensin and virginiamycin supplementation in finishing diets with distiller dried grains plus solubles on growth performance and digestive function of steers

Abstract: Two trials were conducted to evaluate the influence of virginiamycin (26 mg/kg) and monensin (34 mg/kg) supplementation of a steam-flaked corn-based finishing diet containing 15% distiller dried grains plus solubles (DDGS) on growth performance and digestive function. In Trial 1, 135 steers (257 ± 21 kg) were used to evaluate treatment effects on 145-d growth performance. There were no treatment effects (P > 0.20) on dry matter intake (DMI). Antibiotic supplementation tended to increase average daily gain (ADG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
35
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 42 publications
11
35
2
5
Order By: Relevance
“…The trend to greater hot carcass weight obtained with the MON0 diet compared to control diet agrees with the study of Montano et al (2015). The trend to greater hot carcass weight obtained with the MON0 diet compared to control diet agrees with the study of Montano et al (2015).…”
Section: Whole Study Period (0-110 Days)supporting
confidence: 85%
See 1 more Smart Citation
“…The trend to greater hot carcass weight obtained with the MON0 diet compared to control diet agrees with the study of Montano et al (2015). The trend to greater hot carcass weight obtained with the MON0 diet compared to control diet agrees with the study of Montano et al (2015).…”
Section: Whole Study Period (0-110 Days)supporting
confidence: 85%
“…In the present study, the increase in dietary net energy (maintenance and gain) resulting from the combination of increasing doses of MON with VM may have had a positive impact on the gain : feed ratio. Montano et al (2015), using MON or VM, observed an increase of 9% and 11%, respectively, in dietary net energy for maintenance. Barreras et al (2013) obtained an increase in dietary net energy for maintenance (3% more) and gain (4% more) using MON, while Salinas-Chavira et al (2009) observed a 5% increase in dietary net energy with the use of VM.…”
Section: Whole Study Period (0-110 Days)mentioning
confidence: 97%
“…In experiments with feedlot calves, no differences were found for hot carcass weight or hot carcass yield of animals supplemented with virginiamycin (MONTANO et al, 2015;LEMOS et al, 2016;NAVARRETE et al, 2017). In a trial with feedlot sheep receiving 60: 40 concentrate: roughage ratio diets, treatments using banana pseudostem hay as roughage provided better results compared to those with Cynodon sp.…”
Section: Discussionmentioning
confidence: 89%
“…As such, in a high-grain diet, it increases pH, reduces ammoniacal nitrogen, and cause no changes in the population of fibrolytic bacteria (GUO et al, 2010). In feedlot Holstein calves, virginiamycin improved feed conversion (SALINAS-CHAVIRA et al, 2016) and increased the amount of dietary protein reaching the duodenum (MONTANO et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Deswysen, Ellis, Pond, Jenkins, and Connelly (), sodium monensin can decrease the ruminal turnover of solids and liquids, affecting rumen filling, rumination and motility, thus reducing the consumption, in addition to being able to increase the dietary energy content without increasing net energy intake (Benatti, Alves Neto, Oliveira, Resende, & Siqueira, ; Montano, Manriquez, Salinas‐Chavira, Torrentera, & Zinn, ). In this study, calculated dietary net energy for gain was similar between treatment diets (~1.1 Mcal/kg DM, Table ), possibly indicating that there was an increase in the efficiency of energy utilization with reducing in dietary requirements.…”
Section: Discussionmentioning
confidence: 99%